Microstructure evolution in undercooled Ag-50at. %Cu hypereutectic alloy - Shunmeng Zhang; Kai Xiong; Ruixia Yang; Hua Dai; Haijun Wu; Junjie He; Yingwu Wang; Li Wu; Yong Mao (Journal of Materials Research and Technology, 2023)
Ag–Cu alloys, as one type of typical eutectic solders, have been widely used in microelectronic packaging. The welding performance of Ag–Cu solders is closely associated with their microstructures. However, the microstructure evolution of Ag–Cu alloys during solidification is still poorly understood. In this work, a new melt fluxing technique was proposed to investigate the microstructure evolution of undercooled Ag-50at.%Cu hypereutectic alloy. The maximum undercooling of Ag-50at.%Cu alloy can reach up to 135 K. The obtained results show that the microstructures consist of primary dendrite and lamellar eutectic at low undercooling (ΔT – 10 K). With the increase of undercooling, dendrites undergo refining (ΔT < 65 K) and then disappear completely (ΔT = 78 K) and appear again (ΔT = 119 K). It is also discovered that cellular lamellar eutectics formed with ΔT within range of 65 K–78 K. Unexpectedly, irregular microstructures are observed when ΔT > 135 K. Theoretical calculation results indicate that the formation of irregular eutectic is associated with the dendritic fragmentation and eutectic coarsening under larger undercooling (ΔT = 135 K). These results not only elucidate the relationship between the solidification microstructure and undercooling of Ag-50at. %Cu hypereutectic alloys but also has positive significance for other hyper-eutectic systems.